Benign Mixed Epithelial and Stromal Tumor of the Kidney - A. Işin Doğan Ekici; Sinan Ekici; Bora Gürel; Gülçin Altinok; Ilhan Erkan; Yücel Güngen (The Scientific World Journal)
A 51-year-old, perimenopausal, female patient with 1-month history of right flank pain who was diagnosed with a renal mass and underwent nephron-sparing partial nephrectomy is presented. The renal mass was found to be a benign, biphasic tumor composed of an epithelial component, consisting of ducts of variable size scattered within a mesenchymal component, composed of spindle cells arranged in sheets and fascicles. No atypia, mitosis, or necrosis was found. The spindle component shows desmin, smooth muscle actin, and estrogen and progesterone receptor positivity immunohistochemically. The diagnosis of benign mixed epithelial and stromal tumor of the kidney is rendered. No recurrent disease has been detected during 2 years of follow up.